2000
DOI: 10.1002/(sici)1097-4628(20000110)75:2<256::aid-app8>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparative spectroscopic study of the modification of cellulosic materials with different coupling agents

Abstract: ABSTRACT:The reactions of two cellulosic materials (an industrial cellulosic by-product from a Kraft pulp mill facility and a reference material) with three coupling agents, used to improve compatibility between cellulosic reinforcements and thermoplastic matrices, were studied by diffuse reflectance Fourier-transform infrared (DRIFT) spectroscopy and diffuse reflectance ultraviolet-visible spectroscopy. A maleated polypropylene wax (Epolene E-43™) and two silanes (N-2-aminoethyl-3-aminopropyltrimethoxysilane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Absorption bands in the region 1500-1600 cm À 1 could be assigned to the aromatic rings of lignin, 1371 cm À 1 to deformation vibrations of CH 2 in xyloglucans, 1426 cm À 1 to bending vibrations of CH 2 of cellulose, 1738 cm À 1 -stretching vibrations of esters in pectins (Kacurakova et al, 2002). Peaks at 1510Peaks at , 1460Peaks at , 1420Peaks at , 1270Peaks at , 1230Peaks at , 1130 cm À 1 are typical for lignin (Matias et al, 2000;Zancada et al, 2003). The broad band with maximum at 2905 cm À 1 is assigned to CH stretching vibrations in cellulose (Marchessault and Liang, 1960).…”
Section: Ir Spectra Of Wood Chipsmentioning
confidence: 99%
“…Absorption bands in the region 1500-1600 cm À 1 could be assigned to the aromatic rings of lignin, 1371 cm À 1 to deformation vibrations of CH 2 in xyloglucans, 1426 cm À 1 to bending vibrations of CH 2 of cellulose, 1738 cm À 1 -stretching vibrations of esters in pectins (Kacurakova et al, 2002). Peaks at 1510Peaks at , 1460Peaks at , 1420Peaks at , 1270Peaks at , 1230Peaks at , 1130 cm À 1 are typical for lignin (Matias et al, 2000;Zancada et al, 2003). The broad band with maximum at 2905 cm À 1 is assigned to CH stretching vibrations in cellulose (Marchessault and Liang, 1960).…”
Section: Ir Spectra Of Wood Chipsmentioning
confidence: 99%
“…Because the properties of such composites depend on the degree of interfacial adhesion as well as the properties of the individual components, the modification of pristine cellulose might play a key role in the cellulosic polymer composites. [13][14][15] Numerous research groups have been performed to enhance the interfacial adhesion for efficient transfer of stress from the matrix to the fibers, using physical treatments [16][17][18] as well as chemical treatments [1,[19][20][21][22][23] (pretreatment of fiber surfaces by coupling agents, such as silanes and isocyanates, and/or modification of the matrix by grafting with reactive moieties, such as acrylic acid, acrylic esters, maleic anhydride, etc.). Of all these attempts, maleic anhydride grafted polyolefins were found to be one of the most efficient for a composite of cellulose fibers and polyolefin matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The only exception to this state of affairs, before our work, was a thorough study by Herrera-Franco and co-workers [8], which clearly showed that prehydrolyzed siloxanes only reacted with the surface of cellulose fibers (≡Si-OH + ≡C-OH) at high temperature. More recently, Matias et al have confirmed the occurrence of this reaction using diffuse reflectance FTIR and UV-vis spectroscopy [9].…”
Section: Introductionmentioning
confidence: 99%